Penetapan Diversi terhadap Anak yang Terlibat Narkotika - Mita Dwijayanti (Faculty of Law Hang Tuah University, 2017)
Diversion means the diversion of crime problems from legal process to being outside the legal process. The issues raised in this paper are the Arrangement of the Diversion of Children Involved in Narcotics Crime; and how the judge decides against children who are dealing with the law in the order to save the best interests of the child. In its implementation, although this diversion is applicable to save children and the judicial process but not fully implemented because of Law No. 11 Year 2012 have the terms and conditions of the Diversion, one of which is the assumption of children who commit a narcotic crime is not allowed to complete Diversion, children in conflict with the law can damage the public system, public issues as a result of the child's mischief, a children facing the law should enter the Penal Institution.